One more functional equation

Algebra Level 3

Find the number of functions f : R R f:\mathbb{R} \rightarrow \mathbb{R} such that f ( x y ) = f ( x ) f ( y ) f ( x y ) f\left( {x - y} \right) = f\left( x \right) \cdot f\left( y \right) \cdot f\left( {\frac{x}{y}} \right) for all x , y R x,y \in \mathbb{R} , y 0 y \ne 0 .

Note: R \mathbb{R} denotes the set of real numbers.

Inspiration

1 0 3 4 2 infinitely many

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

Let P ( x , y ) P(x,y) be the statement f ( x y ) = f ( x ) f ( y ) f ( x y ) f\left( {x - y} \right) = f\left( x \right) \cdot f\left( y \right) \cdot f\left( {\frac{x}{y}} \right) .

P ( 0 , 1 ) f ( 1 ) = f 2 ( 0 ) f ( 1 ) ( 1 ) P\left( {0,\;1} \right) \Rightarrow f\left( { - 1} \right) = {f^2}\left( 0 \right)f\left( 1 \right)\ \ \ \ \ \ \left( 1 \right)

P ( 0 , 1 ) f ( 1 ) = f 2 ( 0 ) f ( 1 ) ( 1 ) f ( 1 ) = f 4 ( 0 ) f ( 1 ) { f ( 1 ) = 0 or f ( 0 ) = ± 1 P\left( {0,\; - 1} \right) \Rightarrow f\left( 1 \right) = {f^2}\left( 0 \right)f\left( { - 1} \right)\mathop \Rightarrow \limits^{\left( 1 \right)} f\left( 1 \right) = {f^4}\left( 0 \right)f\left( 1 \right) \Rightarrow \begin{cases}f(1)=0\\\text{or}\\f(0)=\pm 1\end{cases}

If f ( 1 ) = 0 f\left( 1 \right)=0 , then P ( x + 1 , 1 ) f ( x ) = f 2 ( x + 1 ) f ( 1 ) f ( x ) = 0 , x R P\left( {x + 1,\;1} \right) \Rightarrow f\left( x \right) = {f^2}\left( {x + 1} \right)f\left( 1 \right) \Rightarrow f\left( x \right) = 0,{\text{ }}\forall x \in \mathbb{R} . Hence, f 0 \boxed{f \equiv 0} is one solution, since it satisfies P ( x , y ) P(x,y) .

If f ( 1 ) 0 f\left( 1 \right)\ne0 , then f ( 0 ) = ± 1 f\left( 0 \right)=\pm1 . Exploring this case we have:

P ( 1 , 1 ) f ( 0 ) = f 3 ( 1 ) P\left( {1,\;1} \right) \Rightarrow f\left( 0 \right) = {f^3}\left( 1 \right) , thus, f ( 1 ) = f ( 0 ) = 1 f\left( 1 \right) = f\left( 0 \right) = 1 , or f ( 1 ) = f ( 0 ) = 1 f\left( 1 \right) = f\left( 0 \right) = -1 .

In any case, for x 0 x \ne 0 , P ( x , x ) f ( 0 ) = f 2 ( x ) f ( 1 ) f 2 ( x ) = 1 , P\left( {x,\;x} \right) \Rightarrow f\left( 0 \right) = {f^2}\left( x \right)f\left( 1 \right) \Rightarrow {f^2}\left( x \right) = 1, which is also true for x = 0 x=0 .

P ( x + 1 , 1 ) f ( x ) = f 2 ( x + 1 ) f ( 1 ) f ( x ) = f ( 1 ) P\left( {x + 1,\;1} \right) \Rightarrow f\left( x \right) = {f^2}\left( {x + 1} \right)f\left( 1 \right) \Rightarrow f\left( x \right) = f\left( 1 \right) , for all x R x \in \mathbb{R} .

The last leads us to two more solutions: f 1 \boxed{f \equiv 1} , or f 1 \boxed{f \equiv -1} , which both satisfy P ( x , y ) P(x,y) .

To conclude, the answer is 3 \boxed{3} .

Mark Hennings
Apr 26, 2020

Putting x = 0 x=0 we see that f ( y ) = f ( 0 ) 2 f ( y ) f(-y) = f(0)^2f(y) for nonzero y y , which means that f ( 0 ) 4 f ( y ) = f ( y ) f(0)^4f(y) = f(y) for all nonzero y y . Thus either f ( 0 ) 4 = 1 f(0)^4 = 1 , so that f ( 0 ) = ± 1 f(0) = \pm1 , or else f ( y ) = 0 f(y) = 0 for all nonzero y y . But then f ( 0 ) = f ( 1 ) f ( 1 ) f ( 1 ) = 0 f(0) = f(1)f(1)f(1) = 0 , so that f 0 f \equiv 0 (one solution)

Suppose that f ( 0 ) = 1 f(0) = 1 . Then f ( y ) = f ( 0 ) 2 f ( y ) = f ( y ) f(-y) = f(0)^2f(y) = f(y) for all nonzero y y , and hence for all y y . Also, putting x = y x=y we see that 1 = f ( 0 ) = f ( x ) 2 f ( 1 ) 1 = f(0) = f(x)^2f(1) for all nonzero x x . In particular f ( 1 ) 3 = 1 f(1)^3 = 1 , so that f ( 1 ) = 1 f(1) = 1 , and hence f ( x ) 2 = 1 f(x)^2 = 1 for all x x . But then f ( x ) = f ( 1 2 x ) f ( 1 2 x ) f ( 1 ) = f ( 1 2 x ) 2 f ( 1 ) = 1 f(x) = f(\tfrac12x)f(-\tfrac12x)f(-1) = f(\tfrac12x)^2f(-1) = 1 for all nonzero x x , and hence f 1 f \equiv 1 (a second solution).

If f ( 0 ) = 1 f(0)=-1 g ( x ) = f ( x ) g(x) = -f(x) is another solution of the functional equation with g ( 0 ) = 1 g(0) = 1 , so that g 1 g \equiv 1 as above. Thus f 1 f \equiv -1 (the third and final solution).

Thus here are exactly 3 \boxed{3} solutions, all constant.

Nice solution! Thanks for posting. Just one remark: The functional equation holds for all real values of x, but obviously for y 0 y \ne 0 (something I had also overlooked on the original text of the problem and added now). Concequently, the relations you get in your solution regarding y y hold for nonzero values. This may slightly differ the way gou get your answers.

Thanos Petropoulos - 1 year, 1 month ago

Log in to reply

A very minor adjustment to the first paragraph fixes that.

Mark Hennings - 1 year, 1 month ago
Tom Engelsman
Apr 25, 2020

In the case of constant functions f ( x ) = C f(x) = C , we have C = C 3 C 3 C = C ( C + 1 ) ( C 1 ) = 0 C = 0 , ± 1 C = C^3 \Rightarrow C^3 - C = C(C+1)(C-1) = 0 \Rightarrow C = 0, \pm1 .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...